El enfoque espacial en la Economía Política - Popescu, Oreste (1959)
After a brief introduction dealing in big lines with the economic thought of the classical and neo-classical schools the author proceeds to analyses the progress achieved in the last 25 years. The first important progress was the construction of the market morphology followed by the macroeconomic approach culminating in KEYNES works, by LEONTIEF'S input-output model, the operational research, the linear programming and the theory of games. Another fundamental progress was achieved by considering time, both in the short run (business cycles) and the long run (economic growth) which occupies at present a central position in the scientific discussion. Finally, the recent intent to improve the one point economic model led to the spatial approach. Thus one can say that modern economic thought developed in three big directions: the first one is formed by the study of the substance of economic phenomena, the second considers time and the third includes space in its approach to economics.